Pathogens, Weather Shocks and Civil Conflicts. (9th June 2017) - Cervellati, Matteo; Sunde, Uwe; Valmori, Simona
Abstract : This article documents a statistically strong and quantitatively relevant effect of high exposure to infectious diseases on the risk of civil conflicts. The analysis exploits data on the presence and endemicity of multi‐host vector‐transmitted pathogens in a country, which is closely related to geo‐climatic conditions due to the specific features of these pathogens. Exploiting within‐country variation over time shows that this effect of pathogen exposure is significantly amplified by weather shocks. The results indicate health shocks and the outbreak of epidemics as a potential channel, while we find no evidence that the effect works through alternative channels like income, population dynamics, or institutions.